2011
DOI: 10.1016/j.avsg.2011.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Exhaled Volatile Compounds Following Acute Superior Mesenteric Artery Occlusion in a Pilot Rat Study

Abstract: Background Prompt diagnosis and treatment of acute mesenteric ischemia (AMI) requires a high index of suspicion for timely management. Poor clinical outcomes and delays in surgical treatment are demonstrated even in modern clinical series. Recognition of exhaled volatile organic compounds (VOC’s) specific to AMI may facilitate early detection and diagnosis and improve patient outcomes. Study Design Adult Wistar Rats (n=5) were intubated and anesthetized and control tracheostomy breath samples were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 24 publications
(28 reference statements)
0
18
0
Order By: Relevance
“…They are the main component in plants essential oils and have a broad spectrum in antimicrobial activity ( 62 ). It was reported that farnesene play a significant role during oxidative injury of eukaryotic cells ( 63 ). Sorbic acid, a food preservative and feed additive ( 64 ), could inhibit the dehydrogenase system of bacteria preventing their reproduction ( 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…They are the main component in plants essential oils and have a broad spectrum in antimicrobial activity ( 62 ). It was reported that farnesene play a significant role during oxidative injury of eukaryotic cells ( 63 ). Sorbic acid, a food preservative and feed additive ( 64 ), could inhibit the dehydrogenase system of bacteria preventing their reproduction ( 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are two animal studies to VOC detection of the changes in metabolic activity following ischemia. The first used an occlusive model (SMA occlusion) and detected various VOC's during ischemia (71). A second study studied the effects of hypovolemic shock in VOC patterns in rats and detected different molecules in early ischemia, reperfusion and during recovery (72).…”
Section: Volatile Organic Compounds (Voc's)mentioning
confidence: 99%
“…The analysis of VOCs in exhaled air is a non-invasive technique that has already been demonstrated to differentiate between multiple clinical conditions and healthy subjects, including inflammatory bowel disease and non-alcoholic steatohepatitis 31. In 2011, a pilot study on the analysis of VOCs in rats following acute superior mesenteric artery (SMA) occlusion identified a small cluster of VOCs that increase during ischaemic bowel injury 32. Other studies have explored the possibility of monitoring exhaled methane (CH4) concentrations in order to detect SMA malperfusion 33.…”
Section: Introductionmentioning
confidence: 99%